EFFECT WORKLOAD, EXPERIENCE AND PROFESSIONAL AUDITOR VIGILANCE AGAINST FRAUD DETECTION (Empirical Study On Public Accounting Firm in South Jakarta area) - Yessie, Afly (Archives of Business Research, 2020)
Abstract This study aims to examine the effects of the workload, experience, and professional awareness of auditors on the detection of fraud. This research was conducted on auditors working at the Public Accountant Firm (KAP) of the South Jakarta region registered with the Indonesian Institute of Certified Public Accountants (Certified) in 2018 using questionnaires. The results of the study indicate that the auditor’s experience and professional vigilance has a significant effect on fraud detection. While the workload does not Significantly influence of fraud detection.